Strengthening Moral Education In Alpha Generation Students At Mis An-Nur Kutilang - Asyraf Hasibuan, Khofifah Rizkina; Nasution, Wahyudin Nur (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
Moral education is a fundamental aspect in the formation of the character of Alpha generation students, especially in facing the challenges of the current digital and information era, especially at MIS An-Nur Kutilang. The purpose of the research is to find out efforts to strengthen student moral education with the implementation program of integrating moral values in the curriculum, extracurricular activities, and parental support. This study uses a qualitative method with a phenomenological approach. With data collection techniques including observation, interviews and document analysis. The results of the study show that the strengthening of moral education at MIS An-Nur Kutilang is carried out by developing a curriculum that integrates moral values, the implementation of character development programs and the active involvement of parents. Strengthening moral education through this holistic approach contributes to improving students' character and positive behavior, although there are several challenges that need to be overcome. The existence of this article is expected to be one of the sources of reference about moral education